Jamaica: Agri-Business Information System (ABIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Agri-Business Information System (ABIS) is being developed by the Jamaican Rural Agricultural Development Authority (RADA) to provide timely and accurate information for small farmers, to improve the production and marketing of commodities and food pr